Biodiversity and Ecological Structure of Mangrove in Coastal Waters of Dafi Village, Biak Numfor Regency - Manan, Jemmy; Manumpil, Abraham W.; Asaribab, Pilipus Y.; Saleky, Dandi (Sam Ratulangi University, 2023)
The existence and sustainability of mangrove forests have a significant role in the environment and communities around the coast. Mangrove ecosystems also have complex systems including plant and animal organisms that interact with one another and play an essential role in maintaining and protecting the coastline. This research was conducted to analyze the potential for the regeneration of mangrove seedlings in the coastal area of Dafi Village, Biak Numfor Regency. Data collection was carried out using the belt transect method. Analysis of species composition and structure of mangrove vegetation used analysis of species density, relative density, species frequency, relative frequency, and important value index. A total of seven mangrove species were found in the coastal area of Dafi Village, Biak Numfor Regency, consisting of Bruguiera gymnorrhiza, Bruguiera cylindrica, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, and Lumnitzera racemoza. Bruguiera gymnorrizha species had the highest density, frequency, and dominance values, while the lowest relative dominance and dominance were found in Lumnitzera racemoza. The highest IVI tree level values ​​were Ceriops tagal and Bruguiera gymnorrhiza. Mangrove forests in this area are still in natural condition, and the existence of mangrove ecosystems supports the lives of people around the island. Keywords: Coastal waters; Mangrove Ecosystem; Type Dominance; Important Value Value Index Abstrak Keberadaan dan kelestarian hutan mangrove mempunyai peran yang signifikan bagi lingkungan dan masyarakat yang tinggal di sekitar pesisir. Ekosistem mangrove juga memiliki sistem yang kompleks meliputi organisme tumbuhan dan hewan yang saling berinteraksi satu dengan yang lain, dan memegang peranan penting dalam menjaga dan melindungi garis pantai. Penelitian ini dilakukan dengan tujuan menganalisis struktur komunitas mangrove di Perairan Kampung Dafi Kabupaten Biak Numfor.Pengumpulan data ekosistem mangrove dilakukan dengan menggunakan metode belt transek. Analisis komposisi jenis dan struktur vegetasi mangrove menggunakan analisis kerapatan jenis, kerapatan relatif, frekuensi jenis, frekuensi relatif, dan indeks nilai penting. Total tujuh jenis mangrove ditemukan di Pesisir Kampung Dafi Kabupaten Biak Numfor yang terdiri atas jenis Bruguiera gymnorrhiza, Bruguiera cylindrica, Ceriops Tagal, Rhizophora apiculata, Rhizophora mucronata, Rhizophora Stylosa, dan Lumnitzera racemoza. Jenis Bruguiera gymnorrizha memiliki nilai kerapatan, Frekuensi dan dominansi tertinggi, sedangkan dominansi jenis dan dominansi relatif terendah pada mangrove jenis Lumnitzera racemoza. Nilai INP tingkat pohon yang paling tinggi adalah Ceriops tagal dan Bruguiera gymnorrhiza. Hutan mangrove pada kawasan ini masih berada dalam kondisi alami, dan keberadaan ekosistem mangrove menjadi penopang bagi kehidupan masyarakat di sekitar pulau. Kata kunci: Pesisir; Ekosistem Mangrove; Dominansi Jenis; Indeks Nilai Penting